Determination of heavy metal contamination from batik factory in different depth in soil using atomic absorption analysis - Noor, Muhammad Akmal Haji Md (Pusat Pengajian Kesihatan, 2015)
A study was carried out to determine heavy metal concentration in soil sample from one batik factory located in Kampung Sungai Keladi, Kota Bharu, Kelantan. Five different sites, (site A, B, C, D, E) with each site, six different depth, starting from 10 cm, 20 cm, 30 cm, 40 cm, 50 cm and 60 cm were collected. Copper (Cu), Cadmium (Cd), Chromium (Cr), Lead (Pb) and Iron (Fe) were chosen for heavy metals contaminant study. These heavy metal concentrations were detected by Atomic Absorption Spectrophotometer (AAS). The results indicated that the amount of Cu was the highest in site A (at 30 cm depth), Cd was the highest in site A (almost equally in every depth), Cr was the highest in site B (at 50 cm depth), Pb was the highest in site A (at 20 cm depth), and the last one Fe, was highest in every site and depth. The depth of the soil gave significant amount of heavy metals due to the present of plants. This was because the plant roots contained the ability to absorb these heavy metals. If in a certain soil depth had a various roots of plants, the amount of heavy metals in soil may be low due to their movement into the roots. However, if a certain depth had less roots, the amount of heavy metals in soils may be high, due to the heavy metals could not being absorbed by plants and contaminated the soil in certain depth. In overall, Fe contained the highest mean concentration, with the average of 4723.500 ppm, followed by Pb (72.713 ppm), Cu (20.876 ppm), Cr (12.820 ppm) and Cd (0.813 ppm) respectively. However, the average concentration of these heavy metals were below the U.S. EPA regulatory standard limit.